2021
DOI: 10.3897/herpetozoa.34.e63998
|View full text |Cite
|
Sign up to set email alerts
|

New herpetofaunal records from Gunung Mulu National Park and its surrounding areas in Borneo

Abstract: Gunung Mulu National Park (GMNP) in northwestern Borneo is marked by high species diversity and diverse environments. We present one new amphibian and ten new reptile records from GMNP and its surrounding area. In the records, Asthenodipsas jamilinaisi and Garthius chaseni were newly recorded in the Sarawak State. We also present the first record of Cyrtodactylus muluensis from outside of GMNP and the second record of Opisthotropis typica from the park. Combined with previous information, a total of 108 amphib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 806 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several studies on the diversity, evenness, and dominance of amphibian species in several national parks or lowland rainforest areas in the world have been conducted (Fukuyama et al 2021;Kabanze et al 2023;Kennedi et al 2024;Mouane et al 2024). Kennedi et al (2024) conducted amphibian diversity surveys in the Bukit Baka Bukit Raya National Park (Tanakaya) in West Kalimantan Province, recording 50 amphibian species from nine families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the diversity, evenness, and dominance of amphibian species in several national parks or lowland rainforest areas in the world have been conducted (Fukuyama et al 2021;Kabanze et al 2023;Kennedi et al 2024;Mouane et al 2024). Kennedi et al (2024) conducted amphibian diversity surveys in the Bukit Baka Bukit Raya National Park (Tanakaya) in West Kalimantan Province, recording 50 amphibian species from nine families.…”
Section: Introductionmentioning
confidence: 99%
“…Kennedi et al (2024) conducted amphibian diversity surveys in the Bukit Baka Bukit Raya National Park (Tanakaya) in West Kalimantan Province, recording 50 amphibian species from nine families. Fukuyama et al (2021) found 108 amphibians in Gunung Mulu National Park, showing that several species are exclusive to particular environments in many habitat types. Mouane et al (2024) reported the findings of the amphibians of Anura ordo from three families, including Bufotes boulengeri, Discoglossus pictus, and Pelophylax saharicus, in the Sahara Desert of Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…While these species are currently considered members of the family Natricidae, which contains hundreds of Old and New World aquatic species, they have also been hypothesized to belong to Homalopsidae (Murphy and Voris, 2014), a smaller family of mostly aquatic, mildly venomous snakes, also found across Southeast Asia. Much of Borneo's herpetofauna and its respective natural history is still in the midst of being fully described and understood (Quah et al, 2019;Das and Wong, 2021;Fukuyama et al, 2021). Indeed, Southeast Asia's undescribed diversity promises exciting discoveries, but it is equally worrisome that this diversity may disappear before ever being discovered (Sodhi et al, 2004;Strang and Rusli, 2021).…”
Section: Introductionmentioning
confidence: 99%